Muscle oxygenation during hybrid arm and functional electrical stimulation–evoked leg cycling after spinal cord injury - Hasnan, Nazirah; Mohamad Saadon, Nurul Salwani; Hamzaid, Nur Azah; Teoh, Mira Xiao Hui; Ahmadi, Sirous; Davis, Glen Macartney (Lippincott, Williams & Wilkins, 2018)
This study compared muscle oxygenation (StO 2 ) during arm cranking (ACE), functional electrical stimulation-evoked leg cycling (FES-LCE), and hybrid (ACE+FES-LCE) exercise in spinal cord injury individuals. Eight subjects with C7-T12 lesions performed exercises at 3 submaximal intensities. StO 2 was measured during rest and exercise at 40%, 60%, and 80% of subjects' oxygen uptake (VO 2 ) peak using near-infrared spectroscopy. StO 2 of ACE showed a decrease whereas in ACE+FES-LCE, the arm muscles demonstrated increasing StO 2 from rest in all of VO 2 ) peak respectively. StO 2 of FES-LCE displayed a decrease at 40% VO 2 peak and steady increase for 60% and 80%, whereas ACE+FES-LCE revealed a steady increase from rest at all VO 2 peak. ACE+FES-LCE elicited greater StO 2 in both limbs which suggested that during this exercise, upper- and lower-limb muscles have higher blood flow and improved oxygenation compared to ACE or FES-LCE performed alone.